Russian Mediaeval Studies in the Soviet Era as a Research Problem - Komendová, Jitka (Dějiny – teorie – kritika, 2009)
This article is concerned with contemporary Russian research on Russian Mediaeval Studies in the Soviet era. Historians of Russian Mediaeval Studies faced repression in the twentieth century to an extent and for a length of time and in an intensity not experienced by historians in any other European country of those days. It is therefore understandable that researchers now look at the past of their own field mainly through the lens of the history of repression. Though picture from outside the trampled field of scholarship (historians in particular and the field in general), as well as victims of the totalitarian regime, is in many respects an accurate one, it has pushed to the background the fact that not only ideologists misused topics from history, but so did scholars themselves, who met this ‘social demand’ and actively took part in disciplining their own field. These fundamental questions, however, have previously not been considered in Russian historiography to the extent they deserve.